AMIN ABDULLAH dan PARADIGMA INTEGRASI-INTERKONEKSI - Dewi Masyitoh (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2020)
Abstract. The amin abdulllah’s thought is birth by the background of the dichotomous phenomena between religion and science can’t be united and stand donelike there is dividing wall each other. To finish the problem of dichotomical science, Amin Abdullah put out a paradigm of integration-interconnection that is now used by UIN Sunan Kalijaga to the development og the science. A paradigm of integration-interconnection that connect between religion and science. By integrating of scientific triangle, that are: hadlarah an-nash, hadlarah al-ilm, and hadlarah al falsafah. The religion and science have relevant relantionship to education in university. The paradigm of integration interconnection will be solution to dichotomis between religion and science. The method would be used is deepen of library with a journal, article and other. Journal making addressed to know Amin Abdullah’s though and integration-interconnection’s paradigm.Keywords: Amin Abdullah, Integration-Interconnection Paradigm, UIN Sunan Kalijaga.